2010
DOI: 10.4000/rfp.1896
|View full text |Cite
|
Sign up to set email alerts
|

Single-sex Education: What Does Research Tell Us?

Abstract: La mixité scolaire : une thématique (encore) d'actualité ? Single-sex Education: What Does Research Tell Us? Non-mixité à l'école : que nous dit la recherche actuelle ? La no-mixidad en la escuela: ¿qué nos aprende la investigación actual? Monoedukation in der Schule: was sagt uns die Forschung?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 50 publications
1
33
0
6
Order By: Relevance
“…As girls progress through secondary grades, they become less confident of their academic skills; thus, their career aspirations are narrowed (Morse, 1998;Else-Quest, Hyde & Linn., 2010). Commenting on this scenario, Smyth (2010) suggests that girls need to have positive attitudes to be motivated to achieve in science. Therefore, methods of teaching like cooperative learning ensure equality of treatment and equality of opportunity for boys and girls (Nichol & Boyle, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As girls progress through secondary grades, they become less confident of their academic skills; thus, their career aspirations are narrowed (Morse, 1998;Else-Quest, Hyde & Linn., 2010). Commenting on this scenario, Smyth (2010) suggests that girls need to have positive attitudes to be motivated to achieve in science. Therefore, methods of teaching like cooperative learning ensure equality of treatment and equality of opportunity for boys and girls (Nichol & Boyle, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados muestran que no existen mayores diferencias entre establecimientos mixtos y no mixtos, con excepción de aquellos que tienen enfoque religioso, lo que está en sintonía con los mayores niveles de establecimientos católicos que existirían en los colegios no mixtos. Por otra parte, al igual que la evidencia internacional, los datos para Chile indican que los colegios no mixtos tienden a ser más selectivos en sus procesos de admisión, ya sea según características familiares como por habilidades de los estudiantes (Smyth, 2010).…”
Section: Resultsunclassified
“…Esto implica que, de 12 resultados de rendimiento académico analizados, solo en uno se detectan diferencias a favor de los establecimientos no mixtos. En otras palabras, luego de controlar por aspectos socioeconómicos, académicos y criterios de selección del establecimiento, las diferencias por composición de género desaparecen 3 , tal como ha sugerido distinta evidencia anglosajona (hannan et al, 1996;Smyth, 2010). De esta forma, serían los arreglos institucionales del establecimiento, junto con otras formas de composición escolar (especialmente la socioeconómica), los que producen las diferencias entre ambos tipos de establecimientos.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…The work is focused on writing and reading, while this research is on speaking skill. Smyth (2010) found that single-sex school is sufficient for both males and females achievement. Male students are more likely to study a female subject in a single-sex classroom.…”
Section: Introductionmentioning
confidence: 98%